Exclusive Breastfeeding among Canadian Inuit: Results from the Nunavut Inuit Child Health Survey ... - McIsaac, Kathryn E.; Lou, Wendy; Sellen, Daniel; Young, T. Kue (University of Alberta Library, 2014)
"Background: Very little population-based research has been conducted around the exclusive breastfeeding practices of Inuit Canadians. Objectives: This research aims to assess the distribution of exclusive breastfeeding among Inuit Canadians and to identify factors associated with exclusive breastfeeding as recommended. Methods: We use data from 188 infant-mother dyads who completed the Nunavut Inuit Child Health Survey, a cross-sectional, population-based survey of Inuit children aged 3 to 5 years. A series of multinomial logistic regression models were run to identify factors associated with 4 exclusive breastfeeding durations (≤ 1 month, > 1-< 5.5 months, 5.5-6.5 months, and > 6.5 months)." (as cited in abstract) ...